Comparative Evaluation of Apparent Diffusion Coefficient Values of White Matter Surrounding the Heterotopia in Children With Unilateral Subependymal Heterotopia - Eroglu, Yesim; Kara, Kevser Tuncer (Springernature, 2022)
Introduction: To compare the apparent diffusion coefficient (ADC) values of the white matter around heterotopia in children with unilateral subependymal heterotopia with those of the symmetrical normal cerebral hemisphere and control group. Methods: Between January 2011 and September 2021, 15 pediatric patients with unilateral focal subependymal heterotopia among 47 patients with heterotopia detected in brain magnetic resonance imaging (MRI) in our hospital were included in the study. The control group consisted of 15 age- and sex-matched children with normal neurological examination and normal brain MRI. In brain MRIs, ADC value was measured from the white matter around the heterotopia area and from the opposite cerebral hemisphere matched to the location, and from the bilateral location-matched white matter of the control group. The area of heterotopia was measured on axial T1-weighted MRI. The data were evaluated statistically. Results: There were eight girls and seven boys in the heterotopia group. The median age was 5.00 (min: 3, max: 14). There was no statistically significant difference between the ADC values of the heterotopia side and contralateral white matter of the heterotopia group. In addition, no statistically significant difference was found between the heterotopia side and opposite sides of the heterotopia and control groups ADC values. Conclusion: According to the findings of this study, no difference was found in the ADC values of the white matter around the lesion in children with subependymal heterotopia compared to the opposite cerebral hemisphere and control groups.
Keywords: children; white matter; apparent diffusion coefficient (adc); diffusion-weighted imaging; subependymal heterotopia